EFEKTIVITAS PELAKSANAAN PROGRAM AYO NABUNG SAMPAH DALAM MENJAGA DAN MEMELIHARA KEBERSIHAN LINGKUNGAN DI KECAMATAN MAESA KOTA BITUNG - PUTRI, AYUNDA; LENGKONG, FLORENCE DAICY; LONDA, VERY (Sam Ratulangi University, 2018)
The aims of this research is to examine the effectiveness of implementation AyoNabung Sampah program in maintaining environmental cleanliness in the subdistrict of Maesathe city of Bitung. This research use descriptive qualitative approach with theory of effectivenessby Sondang Siagian (2000). The informants of this research are the parties involved in theimplementation of the Ayo Nabung Sampah program in Maesa subdistrict. The collectiontechniques used interviews and documentation and the data analyzed can be done by datareduction, data presentation, and resulting the conclution of the data. The results showed thatthe Ayo Nabung Sampah program already operating effectively enough. It can be seen from theclarity of objectives to be achieved, goal achievement strategy, analysis process and the steadypolicy formulation, good planning, preparation of appropriate programs, and the availability ofinfrastructure. However, there are still two imdicator are didn’t optimal, that is goalachievement strategy, the strategies used in this case are socialization and promotion, thesocialization and promotion carried out are not optimal because the mindset and behavior of thesociety are not able tp be changed. the socialization and promotion carried out are not optimal isalso impact on not understanding the society and also external parties regarding the purpose ofthis program. And the second indicator is the availability of infrastructure in Kekenturan SatuUrban village are still did’t optimal.Keywords: Effectiveness, Ayo Nabung Sampah program